Trends in childhood measles vaccination highlight socioeconomic inequalities in Vietnam - Kien, Vu Duy (Int J Public Health, 2016)
OBJECTIVES: To describe trends in measles vaccine coverage rates and their association with socioeconomic characteristics among children from age 12 to 23 months in Vietnam from the year 2000 to 2014. METHODS: Data were drawn from the Vietnam Multiple Indicator Cluster Surveys in years 2000, 2006, 2011, and 2014. Concentration indices were used to determine the magnitude of socioeconomic inequalities in measles vaccine coverage. Associations between measles vaccine coverage and relevant social factors were assessed using logistic regression. RESULTS: Socioeconomic inequalities in measles vaccine coverage rates decreased during 2000–2014. Children belonging to ethnic minority groups, having mothers with lower education, and belonging to the poorest group were less likely to receive measles vaccine; although, their vaccine coverage rates did increase with time. Measles vaccine coverage declined among children of mothers with more education and belonging to the wealthiest socioeconomic group. CONCLUSIONS: Understanding the social factors influencing adherence to recommend childhood vaccination protocols is essential. Attempts to regain and retain herd immunity must be guided by an understanding of these social factors if they are to succeed.